THE RELATIONSHIP BETWEEN STUDENTS' KNOWLEDGE ABOUT SEX WITH STUDENTS' ATTITUDES TOWARDS DATING ACTIVITIES - Siregar, Ineke Putri; Chastanti, Ika; Sari, Novi Fitriandika (Research and Development Journal of Education, 2025)
Knowledge about sex is an important aspect in shaping students' attitudes towards behaviors related to interpersonal relationships, including dating activities. This study aims to identify the relationship between students' level of knowledge about sex and their attitudes towards dating. The subjects were counseling teachers and students of Kemala Bhayangkari Rantauprapat Private High School Students. This study used a quantitative approach by distributing questionnaires to a sample of Kemala Bhayangkari Rantauprapat Private High School Students. Sampling technique using purposive sampling. Data collection techniques were carried out through interviews, observations and questionnaires. The results of the study on sex knowledge of class X students were higher (84.25%) compared to class XI (71.1%) and XII (63.45%). The correlation test results showed that there was no significant relationship (0.296, p = 0.05) between sexual knowledge and dating activities. This indicates that although students have knowledge about sex does not directly affect dating activities. This finding indicates that other factors may be more dominant in shaping students' attitudes towards dating, such as social norms, environmental influences, or family values.